CAPITAL. - Sweeney, Henry W. (The Accounting Review, 1933)
This article discusses the economic benefits of capital. The preservation of a proper distinction between capital and income is the fundamental problem of accounting and the aspects of capital are a prerequisite to sound accounting development. A distinction between the capital that serves as an agent of production and the capital that serves as a means of directly satisfying the wants of man is considered desirable, the former may be called "production capital", and the latter, "consumption capital." Modern methods of business, accounting, and finance, as previously suggested, requite all capital to be measured in the common standard of value used throughout the economic community. The substance of capital is usually measured with reference to the ability of capital to command some economic goods; and this ability depends upon the relationship between the monetary amount of the capital and the monetary amount of the particular economic goods. When the valuation procedure selects productivity as the principal explanation of the existence of capital and then values the capital at the present worth of the estimated income obtainable, the process is frequently called capitalization.